Plasma biomarkers of pulmonary hypertension identified by Fourier transform infrared spectroscopy and principal component analysis. Issue 7 (20th January 2015) - Staniszewska-Slezak, Emilia; Fedorowicz, Andrzej; Kramkowski, Karol; Leszczynska, Agnieszka; Chlopicki, Stefan; Baranska, Malgorzata; Malek, Kamilla
Abstract : In this work FTIR studies on blood plasma in the rat models of hypertension are reported. Abstract : The main goal of this study was to find specific plasma spectral markers associated with pulmonary arterial hypertension (PAH) induced by monocrotaline injection in rats. FTIR was used to monitor biochemical changes in plasma caused by PAH as compared with the systemic hypertension induced by partial ligation on the left artery and with the control group. Both pathologies, systemic and pulmonary hypertension, induced a unique response in the biochemical content of plasma, mainly related to the composition and secondary structure of plasma proteins. For PAH, β-pleated sheet components of plasma proteins were identified whereas the protein composition in systemic hypertension was dominated by unordered structures. In addition, a higher concentration of tyrosine-rich proteins was found in plasma in PAH than in systemic hypertension. The differences between both pathologies were identified also in terms of lipid composition/metabolism as well as in the content of RNA and glucose, suggesting that lipid peroxidation appears upon pulmonary hypertension development. In summary, this work demonstrates that FTIR spectroscopy supported by principal component analysis (PCA) has the potential to become a fast and non-destructive method for biochemical characterization of plasma that consequently could have a diagnostic significance in pulmonary hypertension.